Practical grounds for belief: Kant and James on religion. (25th January 2018) - Williams, Neil W.; Saunders, Joe
Abstract: Both Kant and James claim to limit the role of knowledge in order to make room for faith. In this paper, we argue that despite some similarities, their attempts to do this come apart. Our main claim is that, although both Kant and James justify our adopting religious beliefs on practical grounds, James believes that we can—and should—subsequently assess such beliefs on the basis of evidence. We offer our own account of this evidence and discuss what this difference means for their accounts of religious belief.